2019
DOI: 10.3390/met9111214
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Thermal, and Acoustic Properties of Aluminum Foams Impregnated with Epoxy/Graphene Oxide Nanocomposites

Abstract: Hybrid structures with epoxy embedded in open-cell aluminum foam were developed by combining open-cell aluminum foam specimens with unreinforced and reinforced epoxy resin using graphene oxide. These new hybrid structures were fabricated by infiltrating an open-cell aluminum foam specimen with pure epoxy or mixtures of epoxy and graphene oxide, completely filling the pores. The effects of graphene oxide on the mechanical, thermal, and acoustic performance of epoxy/graphene oxide-based nanocomposites are report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…When the porosity reaches above 80%, the reflection of sound waves is reduced greatly. [ 28 ] Therefore, most of the sound waves are transmitted to the interior of the graphene porous materials through air circulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the porosity reaches above 80%, the reflection of sound waves is reduced greatly. [ 28 ] Therefore, most of the sound waves are transmitted to the interior of the graphene porous materials through air circulation.…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that the graphene can improve the sound‐absorption properties of composites, and reported that the sound absorption mainly depends on porosities and the morphologies of pores. [ 28–31 ] It is worth noting that the 3D graphene foam has above 95.0% porosity and ultralow density, so it can be used as a kind of sound‐absorbing material. Unfortunately, when graphene foam is subjected to compression, bending, or stretching, it exhibits significant plastic deformation or poor mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Damanik and Lange [8] investigate the effect of multiwalled carbon nanotubes coated with nickel on the foaming behavior and morphology of reinforced AlMg4Si8 foam prepared by a powder metallurgy process. Pinto et al [9,10] present novel aluminum foam-polymer nanocomposite hybrid structures, providing the structural, mechanical, thermal, and acoustic properties. These hybrid structures are prepared by infiltrating an open-cell aluminum foam with a polymer (epoxy [9] and polyurethane foams [10] with or without graphene oxide) to enhance the performance of the resulting hybrid structures.…”
Section: Contributionsmentioning
confidence: 99%
“…Pinto et al [9,10] present novel aluminum foam-polymer nanocomposite hybrid structures, providing the structural, mechanical, thermal, and acoustic properties. These hybrid structures are prepared by infiltrating an open-cell aluminum foam with a polymer (epoxy [9] and polyurethane foams [10] with or without graphene oxide) to enhance the performance of the resulting hybrid structures. The three following contributions are focused on new cellular structures to be applied for structural applications.…”
Section: Contributionsmentioning
confidence: 99%
“…Lattice cored structures such as pyramidal [8,9], corrugated [10,11], Kagome [12], and honeycomb cores [13][14][15] have advantages in load carrying applications; however, after the loading force reaches its peak, core member softening occurs and leads to an immediate and dramatic decline of load-carrying capacity [8]. In contrast, foam structures have excellent energy absorption properties [16][17][18] and functional designs, such as acoustic absorption [19,20] and thermal insulation [21,22], but their mechanical strength is limited due to the microstructure of the core and defects during the foaming process and high porosity [23]. Therefore, designing structures resistant to core member buckling and increasing specific strength and energy absorption are important for applications of lightweight sandwich structures.…”
Section: Introductionmentioning
confidence: 99%